Particle Micronization of Medicinal Plants Extract using Electrospraying - Rizkita, Nadya; Bisma Hendra Setiyawan; Rais Fakhrirazin; Siti Machmudah; Sugeng Winardi; Wahyudiono (Research in Chemical Engineering, 2026)
Phytochemical compounds are non-nutritive plant bioactive components that contribute to disease prevention through their antioxidant and antiinflammatory activities. In this study, particles of polyvinylpyrrolidone (PVP), chitosan, and starch-containing phytochemical compounds from medicinal plant extracts were prepared through an electrospray process. This method is used to increase the bioavailability of phytochemical compounds as well as to facilitate the storage process and durability. The effect of process parameters in this study was investigated, the type of polymers (medicinal plant extract/PVP, chitosan, and starch) and the electric voltage used. Particle characterization and phytochemical properties were evaluated using FTIR, total phenolic content (TPC), total flavonoid content (TFC), and antioxidant activity analyses. The results showed that PVP exhibited the best performance in binding phytochemical compounds from medicinal plants. This was exemplified by the O. aristatus/PVP at an applied voltage of 16 kV, which resulted in the highest total phenolic and flavonoid contents of 0.5816 mg GAE/g sample and 0.7638 mg CE/g sample, respectively. Antioxidant activity, evaluated using antioxidant efficiency (AE), also showed the highest value for the O. aristatus/PVP at 18 kV, reaching 0.8511 min⁻¹. FTIR analysis indicated that PVP was able to physically interact with phytochemical compounds, as evidenced by the overlap between the polymer and extract spectra. In contrast, chitosan and starch exhibited relatively weaker interactions, leading to more limited encapsulation capability and consequently lower retention of phytochemical compounds within the particles.